Bortezomib – first proteasome inhibitor for the treatment of multiple myeloma - Jurczyszyn, Artur; Skotnicki, Aleksander (Contemporary Oncology/Współczesna Onkologia, 2007)
Bortezomib (PS-341) has been the first proteasome inhibitor to enter clinical trials and practice in cancer patients. Based on results of preclinical studies showing that his novel agent directly inhibits the proliferation of myeloma cells, induces their apoptosis and abrogates paracrine tumour growth through alteration of myeloma-stromal cell interactions and nuclear factor-kB- -dependent cytokine secretion, several large phase II and III studies of bortezomib were initiated in patients with advanced relapsed and/or refractory multiple myeloma (MM). Favourable results of these studies led to accelerated approval for use of bortezomib in MM patients who have progressed after at least their second therapy and more recently to expanded approval for second-line use in patients on whom one prior therapy has failed. In the meantime, combination studies of bortezomib with various agents, including dexamethasone, DNA-damaging drugs, thalidomide and lenalidomide, have been designed in patients with both relapsed/refractory and newly diagnosed disease. Bortezomib offers great promise to overcome resistance to conventional therapy and may be the “backbone” for the development of more effective treatment strategies antineoplasmal.